Laser induced elastooptics in novel Bi2O3, and Pr2O3 doped tellurite rich glasses - Lakshminarayana, G.; Kaky, Kawa M.; Jedryka, J.; El-Naggar, A. M.; Albassam, A. A.; Myronchuk, G.; Mahdi, Mohd Adzir (Elsevier, 2016)
We have studied the laser stimulated effects in 70TeO2-10ZnO-10WO3-5TiO2-5Na2O (mol%) glasses doped with 1…5 mol%. of Bi2O3, and Pr2O3, respectively. The photoinduced processes were performed using two coherent beams of 532 nm doubled frequency Nd: YAG pulsed laser at angles varying within 28 to 26 degree. The low-power 532 nm beam has served as a probing one for detection of photoinduced changes. The crucial dependence on the Pr3+ and Bi dopants was observed. This one allows using these compounds for the laser operated optical devices.